Immunisation in children with cancer treated with standard dose chemotherapy- review of evidence - Nirmalya Roy Moulik; Ramandeep Singh Arora (Elsevier, 2020)
The improving outcome of childhood cancers has led to increase in number of survivors needing comprehensive care during and after treatment of cancer. Immunisation is an important tenet of this and is often neglected especially in the resource constrained settings due to preoccupation with treatment and disease related aspects in these children. In this narrative review we review the existing evidence on this important subject. It includes a brief account of the effects of chemotherapy on various components of immune function as well as the current evidence based recommendations on immunisation of children undergoing chemotherapy both during and after end of treatment. It also reviews the literature on recommendations for immunisation of contacts of children undergoing chemotherapy.